Peningkatan Keterampilan Guru Raudhatul Athfal Melalui Pelatihan Mendongeng Di IGRA Kecamatan Banjarsari - Feri Faila Sufa; M Hery Yuli Setiawan; Yassir Aminuddin (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Storytelling skills are a must for early childhood educators. This storytelling training aims to improve the skills of Raudhatul Athfal (RA) teachers in using the storytelling method as a tool to stimulate early childhood language development. The purpose of this activity is to help Teachers of early children education have storytelling skills to stimulate language. The activity was carried out at Teacher Unity of IGRA Banjarsari District, Surakarta, and involved 19 participants from six RA institutions. The methods used in the training include lectures, demonstrations, and hands-on practice. The results of the training showed a significant improvement in storytelling skills among teachers, as well as a positive impact on children's language development. This article describes the training process, evaluation results, and its impact on the quality of learning in RA. Recommendations from this service activity can be developed to other areas based on edutainment so as to provide a more varied method.